2015
DOI: 10.1159/000371691
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inhibiting Ileal Apical versus Basolateral Bile Acid Transport on Cholesterol Metabolism and Atherosclerosis in Mice

Abstract: Background: Bile acid sequestrants have been used for many years to treat hypercholesterolemia by increasing hepatic conversion of cholesterol to bile acids, thereby inducing hepatic LDL receptor expression and clearance of apoB-containing particles. In order to further understand the underlying molecular mechanisms linking gut-liver signaling and cholesterol homeostasis, mouse models defective in ileal apical membrane bile acid transport (Asbt-null) and ileal basolateral membrane bile acid transport (Ostα-nul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…We showed that Asbt -/mice had a 3-fold increase in fecal BA and NS excretion. While it was previously reported that Asbt -/mice have decreased fractional cholesterol absorption (55% versus 74% in WT littermates) (12), it remained unclear whether this could quantitatively account for the strongly increased fecal NS excretion (17,39). Our data show that fractional cholesterol absorption in Asbt -/mice was much lower (~6%), and even similar to that of WT mice treated with ezetimibe (~4%), suggesting that the increase in fecal NS excretion was mainly due to impaired cholesterol (re)absorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that Asbt -/mice had a 3-fold increase in fecal BA and NS excretion. While it was previously reported that Asbt -/mice have decreased fractional cholesterol absorption (55% versus 74% in WT littermates) (12), it remained unclear whether this could quantitatively account for the strongly increased fecal NS excretion (17,39). Our data show that fractional cholesterol absorption in Asbt -/mice was much lower (~6%), and even similar to that of WT mice treated with ezetimibe (~4%), suggesting that the increase in fecal NS excretion was mainly due to impaired cholesterol (re)absorption.…”
Section: Discussionmentioning
confidence: 99%
“…For ezetimibe, the mechanism of inhibition of cholesterol (re)absorption has been directly related to inhibition of NPC1L1, the main protein responsible for cholesterol absorption (38). For Asbt -/inactivation, however, the mechanism of decreased cholesterol (re)absorption has been less clear (39).…”
Section: The Mechanism Of Decreased Cholesterol (Re)absorption In Asbmentioning
confidence: 99%
“…We previously reported that genetic ASBT knockout in mice reduces intestinal fat and cholesterol absorption (29,34,35). In order to determine if the ASBTi treatment had similar effects in the CSAA and CDAA diet-fed mice, we measured fat absorption using the sucrose polybehenate method (20).…”
Section: Asbt Inhibitor Treatment Reduces Intestinal Fat Absorption Imentioning
confidence: 99%
“…http://www.guidetopharmacology.org/GRAC/LigandDisplayForward?ligandId=9996 (rINN) is a highly selective inhibitor of an http://www.guidetopharmacology.org/GRAC/FamilyDisplayForward?familyId=182#960, leading to augmentation of BA levels in the colon and subsequently enhancing colonic motility and secretion 12. In addition, reduced ileal BA reabsorption upregulates hepatic BA synthesis from cholesterol and induces expression of low‐density lipoprotein cholesterol (LDL‐C) receptors on hepatocytes 13. Thus, elobixibat decreases the plasma LDL‐C level.…”
Section: Introductionmentioning
confidence: 99%